Deaths resulting from the use of firearms by police against motor vehicles: Study of cases in Porto, Portugal - Rodrigues, Ezequiel (2017)
The objective of this study was to investigate the terminal ballistics of police shootings in which the bullets went through any motor vehicle structure before fatally wounding the occupants. 6 cases that occurred in Porto district between 1998 and 2013 were studied. The firearms used were 7.65 mm (n = 1) or 9 mm (n = 3) calibre semi-automatic pistols and 9 mm calibre submachine guns (n = 2); the bullets were full metal jacket type. The metal jacket of the collected projectiles was totally or partially destroyed in 3 cases. It exhibited a deformed structure in all cases. The trajectories of the bullets in the vehicles were always more or less linear, even when initial impact was at an oblique angle. The entry holes in the victims' bodies were larger or much larger in size than the calibre of the bullets. They were located, with the exception of one of the cases, in the left half of the body. The trajectories in the victims' bodies were from front to back, in one case, and from back to front in all others. Exit wounds were only found in two cases. Death occurred immediately after the victim was shot only in one case, despite a vital structure has been hit in all cases. The cases studied support the idea that the use of firearms against vehicles with the sole intention of immobilisation entails uncontrollable danger to the lives of the occupants, and especially when done by police forces not specifically trained for that purpose. Therefore, such use of firearms should be avoided.